Technology shocks, employment, and labor market frictions - Federico S. Mandelman; Francesco Zanetti (Federal Reserve Bank of Atlanta, 2008)
Recent empirical evidence suggests that a positive technology shock leads to a decline in labor inputs. However, the standard real business cycle model fails to account for this empirical regularity. Can the presence of labor market frictions address this problem without otherwise altering the functioning of the model? We develop and estimate a real business cycle model using Bayesian techniques that allows but does not require labor market frictions to generate a negative response of employment to a technology shock. The results of the estimation support the hypothesis that labor market frictions are responsible for the negative response of employment.
Keywords: E32; 330; technology shocks; employment; labor market frictions; Technischer Fortschritt; Schock; Arbeitslosigkeit; Arbeitsmarkt; Arbeitsmarktungleichgewicht; Theorie